2021
DOI: 10.1002/ncp.10753
|View full text |Cite
|
Sign up to set email alerts
|

Importance of addressing malnutrition in cancer and implementation of a quality improvement project in a gastrointestinal cancer clinic

Abstract: Malnutrition is exceedingly common in cancer patients, with some of the highest rates seen in gastrointestinal (GI) malignancies. Malnutrition and cachexia in cancer patients is associated with worse quality of life, poor treatment tolerance, and increased morbidity and mortality. The importance of early recognition of malnutrition in cancer patients is key, and numerous screening tools have been validated to aid practitioners in this diagnosis. In this paper, we summarize the importance of identifying and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Overall, evidence of the literature reasonably supports the view that widespread malnutrition can be found in patients with GI malignancies, though it remains an underdiagnosed problem in cancer patients [37][38].…”
Section: Discussionmentioning
confidence: 53%
“…Overall, evidence of the literature reasonably supports the view that widespread malnutrition can be found in patients with GI malignancies, though it remains an underdiagnosed problem in cancer patients [37][38].…”
Section: Discussionmentioning
confidence: 53%
“…Also, although the nutritional deterioration in cancer was the highly complex end result of multiple interactions, our results also suggested that when patients with advanced gastrointestinal cancer with socioeconomic deprivation were well nourished, they could contribute 23.11% to their healthy quality of life (95%CI: 9.67 to 36.56). This re‐emphasizes that early identification of malnutrition in cancer patients and effective nutritional support strategies may be an important predictor of increased quality of life (Levonyak et al, 2022; Vitaloni et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Medical professionals and cancer patients alike believe toxicities are inevitable and general amelioration techniques are often overlooked. Difficulty eating and malnutrition during cancer therapy are common problems that can be assessed with many tools [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. The challenge is to have an acceptable quality and quantity of nutrient intake with minimal toxicity without compromising effective cancer treatment.…”
Section: Drug Combinationsmentioning
confidence: 99%
“…Malnutrition in cancer patients is a common problem. There are many indices and tools to define malnutrition, cachexia, and sarcopenia [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]62,[69][70][71][72][73][74][75][76][77]. Although weight loss from the time of diagnosis is one measure, the quantity and quality of food in the diet and information from the patient generated subjective global assessment (PG-SGA) tool can provide more specific information [35,36,45,51,62,66,[69][70][71][72][73][78][79][80].…”
Section: Review Of Strategies To Improve Eating Behaviors While Receiving Chemotherapy And/or Radiationmentioning
confidence: 99%